The Application of Responsibility Accounting as a Tool for Measuring Management Performance at PT Perkebunan Nusantara IV Regional II Kebun and PKS Adolina Perbaungan - Cindy Erisha Sihombing; Mulatua P Silalahi; Arison Nainggolan; Arthur Simanjuntak (Jurnal Ilmiah Accusi, 2026)
PT Perkebunan Nusantara IV Regional II Kebun Perbaungan operates within a framework that demands the achievement of clearly defined performance targets. Effective implementation of responsibility accounting is expected to improve management performance in conducting company activities, while in turn, effective management performance supports the optimal application of responsibility accounting, enabling the achievement of organizational goals. This study aims to analyze the application of responsibility accounting at PT Perkebunan Nusantara IV Regional II Kebun and PKS Adolina Perbaungan, and to examine how responsibility accounting is utilized as a tool for measuring management performance. A qualitative descriptive methodology was employed, with data collected through observation, interviews, and documentation techniques. The findings reveal that the average realized production costs exceeded the established budget, generating unfavorable variances particularly in palm oil production activities. This indicates that cost control was not yet operating optimally and requires more intensive managerial attention. Nevertheless, the responsibility accounting system functioned effectively as a management performance measurement tool, with evaluations carried out through internal management reports containing production realization data, cost utilization information, and target achievement results, followed by corrective actions for each identified deviation